Neonatal Outcomes of Women with Recurrent Pregnancy Loss from Immunologic Causes in the Philippine General Hospital from 2010-2015 - Chacon, Hyacinth Claire; Mondragon, Alric; Castor, Mary Ann; Recto, Marysia Stella; Casis Hao, Roxanne; Sumpaico, Madeleine (Philippine Journal of Allergy, Asthma and Immunology, 2024)
Background: Recurrent pregnancy loss (RPL) has been classically defined as three consecutive pregnancy losses, which may be associated with several immunologic and non-immunologic etiologies. There are two immunologic mechanisms, autoimmune or alloimmune, of RPL that have drawn much interest in recent years. The direct effects of these immunologic dysregulations on the clinical outcomes of children born from mothers afflicted with Antiphospholipid Antibody Syndrome (APS) or alloimmune causes still need further investigation. Objective: To determine the neonatal outcome of infants born from mothers with RPL from immunologic causes at the Philippine General Hospital (PGH) from 2010-2015. Pregnant women with RPL from immunologic causes are classified as high-risk pregnancies. The results of this study hope to guide physicians in close monitoring and early intervention of mothers with RPL and their neonates. Methodology: This was a retrospective study of neonates born from mothers diagnosed to have immunologic causes of RPL from 2010-2015 at the PGH. All patients born from mothers diagnosed to have an immunologic cause of RPL from 2010-2015 based on the patient database of the section of Allergy and Immunology of the PGH. Results: The prevalence of neonates born from mothers with RPL from identified immunologic causes and unexplained causes among all infants born at the PGH from 2010 to 2015 is 0.18%. There were 5.1% of the neonates that were classified as Classical APS, 63.8% as Obstetric Morbidity associated with Antiphospholipid Antibody Syndrome (OMAPS), and 31% had an unexplained cause. There were no cases classified under other immunologic causes. Most neonates under Classical APS were born live, full-term, via cesarean delivery with a mean birth weight of 2206 ± 539.48 grams with APGAR Score (AS) of 9 and 9. The majority of the neonates under OMAPS were born live, full-term, via cesarean delivery with a mean birth weight of 2537 ± 737.46 grams and AS of 9 and 9. Most of the neonates under the unclassified cause of RPL were born live, full-term via cesarean delivery with a mean birth weight of 2228.75 ± 887.05 grams and an AS of 9 and 9. Conclusion: The majority of these infants born from mothers with RPL from immunologic or unexplained causes had a good birth outcome. Hence, the immunologic cause of RPL has minimal effects on the neonate.